2020
DOI: 10.1016/j.hpb.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of hypovolemic phlebotomy on blood loss and transfusion in liver surgery: a systematic review and meta-analysis

Abstract: Background: Hypovolemic phlebotomy (HP) is a novel intervention that involves intraoperative removal of whole blood (7-10 mL/kg) without volume replacement. The subsequent central venous pressure (CVP) reduction is hypothesized to decrease blood loss and the need for blood transfusion. The objective was to conduct a systematic assessment of the safety and efficacy of HP on blood loss and transfusion in the liver surgery literature. Methods: MEDLINE, EMBASE, and Cochrane Library databases were searched. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
(149 reference statements)
2
12
0
1
Order By: Relevance
“…They concluded that hypovolemic phlebotomy is safe and associated with decreased transfusion in patients undergoing liver surgery with underlining pathology. 50 This finding at least supports the safety of this blood conservation technique in donor liver hepatectomy.…”
Section: Liver Transplantationsupporting
confidence: 52%
“…They concluded that hypovolemic phlebotomy is safe and associated with decreased transfusion in patients undergoing liver surgery with underlining pathology. 50 This finding at least supports the safety of this blood conservation technique in donor liver hepatectomy.…”
Section: Liver Transplantationsupporting
confidence: 52%
“…The use of IOHP was safe, and not associated with more postoperative complications, as supported by a recent meta-analysis. 29 The adversely impacted cancer outcomes observed in transfused patients following hepatectomy 3,[6][7][8] may be due to transfusion-associated immunomodulation (TRIM), characterized by increased regulatory T cells, dysfunctions of natural killer cells and macrophages, and deficient antigen presentation, which in turn may impact healing and anti-cancer immunity. 30,31 Although TRIM may be decreased by depleting allogeneic blood of leukocytes, 32,33 in the modern era, the benefit of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IOHP was safe, and not associated with more postoperative complications, as supported by a recent meta-analysis. 29 …”
Section: Discussionmentioning
confidence: 99%
“…There have been very few trials comparing HP with the standard of care in patients with primarily oncological indications. An RCT comparing HP with standard of care in living donor procurement procedures reported less blood loss with phlebotomy during liver parenchymal resection (140 versus 230 ml; P = 0·034), but found no significant difference in total intraoperative blood loss (403 versus 440 ml; P = 0·257).…”
Section: Discussionmentioning
confidence: 99%
“…Seven other studies reporting on the use of HP in liver surgery were identified in a systematic review, including two RCTs, four retrospective cohort studies of patients undergoing liver resection (3) or liver transplantation (1), and one case series of patients undergoing liver resection. Pooled analysis of studies reporting on patients undergoing HP versus standard of care at the time of liver resection for non‐transplant indications reported that HP was protective of blood loss (–173 (95 per cent c.i.…”
Section: Discussionmentioning
confidence: 99%